Reception of Belic’s learning on word formation in slavic languages - Tešanović, Drago V (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2018)
This paper brings into daylight some relevant facts from word formation, which was one of the central disciplines in Serbian language in the past. This, primarily, show Belic’s works which, in Slavic world, are accepted as the foundation for this discipline. Therefore, prominent Russian from the end of twentieth century return to the theoretical perspectives of A. Belic, in derivatology, so word formation of his time count as the central discipline. Modeled on Belic’s theoretical reviews in derivation, many works by eminent experts in Russian, Czech, and Bulgarian language have appeared.